Biphasic Pattern of Depression and Its Predictors during Pegylated Interferon-Based Therapy in Chronic Hepatitis B and C Patients. Issue 4 (May 2013) - Huang, Yi-Wen; Hu, Jui-Ting; Hu, Fu-Chang; Chang, Ching-Jui; Chang, Han-Yu; Kao, Jia-Horng; Yang, Sien-Sing; Chen, Ding-Shinn
Background: It remains unclear whether depression in chronic hepatitis B (CHB) and chronic hepatitis C (CHC) during pegylated interferon-based therapy is associated with the virus, drug or ethnic background. We aimed to perform a prospective study to evaluate the clinical course of depression and its predictors in consecutive non-cirrhotic CHB and CHC patients of the same ethnicity receiving pegylated interferon-based therapy. Methods: The occurrence and severity of depression were actively assessed by the Hamilton Depression Rating Scale before therapy and at weeks 2, 4, 6, 8, 10, 12 and every 4 weeks during treatment until the end of therapy. Extensive numbers of variables (repeated measurements, time variables and interactions between all variables) were included in generalized estimating equations to analyse the predictors of depression. Results: A total of 158 consecutive patients (73 CHB and 85 CHC patients) were enrolled. Depression (Hamilton Depression Rating Scale ≥11) occurred in a biphasic pattern at treatment weeks 2-10 and weeks 16-36. Treatment weeks <10 predicts more depression, and treatment weeks >12 predicts less depression, suggesting the predictability of the time variable during treatment on depression. Furthermore, CHC or pre-existing depression is an independent predictor of depression in these patients ( P <0.001). Conclusions: Depression occurred in a biphasic pattern during pegylated interferon-based therapy and should be early and actively assessed, especially in patients with CHC or pre-existing depression.